STUDI FENOMENOLOGI: WORK LIFE BALANCE PADA DOSEN WANITA SELAMA PANDEMI COVID-19 - Nurmuliasneny Musa; Moch. Rahadian Hakiem; Adelia Mutiara Deski; Muhammaf Yusuf Shofyan; Anugrah Sabilia; Achmad Chusairi (Jurnal Abdi Insani, 2022)
The Covid-19 pandemic is a phenomenon that causes social disruption, especially in the scope of work, social and organization, regulation that has been imposed by government such as work from home currently become a new culture, especially in Indonesia. This has a significant impact on various stakeholders involved in education field, such as lecturer. Theory that could explain this event, namely work life balance (WLB) is a process to create and maintain a healthy and supportive work environment, which support employees to have a balance between work and personal life. The aim of this study is to explore the personal experience of Work Life Balance on women lecturers during the Covid-19. The method in this study is qualitative phenomenology, was carried out by collecting data through interview with two subjects, namely female lecturers who were married, researchers chose the subject of women lecturers because the subject had to be responsible for domestic and academic responsibilities. This study shows that each subject has similarities in interpreting the present, where they are feel grateful for the conditions that require them to work from home so that they can help children and are grateful that families want to understand and provide awareness to women that their personal and work lives can run smoothly. hand in hand, besides the importance of support for female lecturers. The conclusion of this research.